Expression Profile of Cationic Amino Acid Transporters in Rats with Endotoxin-Induced Uveitis - Yung-Ray Hsu; Shu-Wen Chang; Chang-Hao Yang; Yi-An Lee; Tzu-Yun Kao (Mediators of Inflammation)
Purpose. The transcellular arginine transportation via cationic amino acid transporter (CAT) is the rate-limiting step in nitric oxide (NO) synthesis, which is crucial in intraocular inflammation. In this study, CAT isoforms and inducible nitric oxide synthase (iNOS) expression was investigated in endotoxin-induced uveitis (EIU). Methods. EIU was induced in Lewis rats by lipopolysaccharide (LPS) injection. In the treatment group, the rats were injected intraperitoneally with the proteasome inhibitor bortezomib before EIU induction. After 24 hours, leukocyte quantification, NO measurement of the aqueous humor, and histopathological examination were evaluated. The expression of CAT isoforms and iNOS was determined by reverse transcription-polymerase chain reaction, western blotting, and immunofluorescence staining. Nuclear factor-kappa B (NF-κB) binding activity was evaluated by electrophoretic mobility shift assay. The mouse macrophage cell line RAW 264.7 was used to validate the in vivo findings. Results. LPS significantly stimulated iNOS, CAT-2A, and CAT-2B mRNA and protein expression but did not affect CAT-1 in EIU rats and RAW 264.7 cells. Bortezomib attenuated inflammation and inhibited iNOS, CAT-2A, and CAT-2B expression through NF-κB inhibition. Conclusions. CAT-2 and iNOS, but not CAT-1, are specifically involved in EIU. NF-κB is essential in the induction of CAT-2 and iNOS in EIU.